Type B insulin resistance syndrome with Scleroderma successfully treated with multiple immune suppressants after eradication of Helicobacter pylori infection: a case report. Issue 1 (December 2016) - Yang, Guo-Qing; Li, Yi-Jun; Dou, Jing-Tao; Wang, Bao-An; Lu, Ju-Ming; Mu, Yi-Ming
Abstract Background Type B insulin resistance is a rare autoimmune disease characterized by the presence of autoantibodies against the insulin receptor. Helicobacter pylori (H pylori) infection may play a causative role in the autoimmune diseases. Case presentation Here, we present a rare case of a 48-year old female patient, who had type B insulin resistance with systemic scleroderma and was successfully treated with multiple immune suppressants after eradication of Helicobacter pylori infection. Conclusion The present case suggests H pylori infection-related pathological mechanism may contribute to type B insulin resistance syndrome and autoimmune disorders. Treatment toward H pylori may be helpful to relieve syndrome of type B insulin resistance for H pylori positive patients.